Report of the Working Group on Technical Education and Vocational Training - Planning Commission (Planning Commission, 1960)
Planning Commission in pursuance of the recommendations of the National Development Council at their meeting held in New Delhi on November 8 & 9, 1958, decided to appoint Working Groups for different subjects for considering various issues relating to the third live year plan. A decision was taken at a meeting of the Secretaries of different Ministries of the Government of India on December 4 & 5, 1958, that Working Groups of representative members and experts be appointed in different subjects for the purpose. The Working Group on Technical Education and Vocational Training was appointed in February 1959, with the personnel mentioned in Appendix-I and with Prof. M. S. Thacker, Secretary, Ministry of Scientific Research & Cultural Affairs, as the Chairman. It was agreed that the Working Group should include a few persons outside the Government, for instance.
Government of India Planning Commission